Analysis of students difficulties in mathematics problem-solving ability on number pattern material - Nur Mahsarah Rahadatul Aisy; Mulyono; Walid (Jurnal Pijar Mipa, 2022)
This research aims to analyze and describe students' difficulties in solving mathematical problem-solving abilities on number pattern material. The research method is qualitative research, with the research subjects being grade eight students in one of the schools in the city of Semarang in the academic year 2022/2023. The research instrument was in the form of a mathematical problem-solving ability test and interviews. The mathematical problem-solving ability test indicator uses the indicators proposed by NCTM, with the stages of problem-solving according to Polya. The results showed that students with the concept difficulty type could only understand the problem. The student with the principal difficulty type could carry out the strategy planning stage. Finally, the students with the conceptual difficulty type have been able to implement the stage of planning strategies in solving mathematical problems.